Monitoring antibiotic‐resistant enterobacteria faecal levels is helpful in predicting antibiotic susceptibility of bacteraemia isolates in patients with haematological malignancies. Issue 7 (July 2015) - Woerther, Paul‐Louis; Micol, Jean‐Baptiste; Angebault, Cécile; Pasquier, Florence; Pilorge, Sylvain; Bourhis, Jean‐Henri; de Botton, Stéphane; Gachot, Bertrand; Chachaty, Elisabeth
Abstract : N/A: Delay of active antimicrobial therapy in haematological patients with Gram‐negative bacilli bacteraemia during profound neutropenia exposes them to increased morbidity and mortality. The digestive tract is the main source of enterobacteria causing bacteraemia in these patients. We thus evaluated the usefulness of broad‐spectrum beta‐lactam resistant enterobacteria (BSBL‐RE) faecal shedding assessment in forecasting the susceptibility to BSBLs of the strains isolated from blood cultures. From 2002 to 2011, neutropenic haematological patients with bacteraemia caused by enterobacteria who had a stool culture during the previous 7 days were retrospectively included. BSBL‐RE intestinal carriers were compared with non‐carriers in terms of clinical and microbiological criteria. One hundred and four patients were included and 16 of them (15.4 %) were BSBL‐RE carriers. Multivariate analysis showed that BSBL‐RE carriage was independently associated with BSBL‐RE identified in blood cultures ( P < 0.001) and the use of carbapenems as empirical treatment of the bacteraemia ( P = 0.008). Sensitivity, specificity, and the positive and negative predictive values of the test were 80 %, 91 %, 50 % and 98 %, respectively. Among the carriers, those with the highest level of BSBL‐RE carriage were also those with the highest risk of bacteraemia due to BSBL‐RE ( P < 0.001). Close monitoring of BSBL‐RE intestinal carriage may help to choose the most appropriate initial antimicrobial treatment for neutropenic haematological patients with bacteraemia.